Variable inertia training: Optimization of explosive-power exercises with robotic-resistance strength machines - Biscarini, A.; Contemori, S. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
Strength training machines with computer-adjustable resistance mechanisms can simulate external resistance of different kinds (i.e. gravitational, elastic, and viscous) and magnitude R, and different levels of inertial force (the product of the resistance mass m and its acceleration). Notably, the simulated levels of R and m can be freely adjusted, during movement, independently of each other. In this study, the authors have performed a numerical simulation of exercises for explosive power to analyze the kinematic and kinetic effects of resistances that combine different levels of R and m (i.e. different levels of external resistance and inertial force). A progressive increase in m gradually enhances the peak user`s force and reduces the peak acceleration at all resistances R, enhances and shifts later in time the peak power at low resistances, and reduces the mean power at high resistances. The mass m also induces a rate of force development at the beginning of movement in a time frame which becomes progressively longer with higher values of m. Complete lack of mass m would be needed in the final phase of the movement to attain an effective training stimulus for high-velocity strength. In light of this evidence, the authors have devised a new training modality for explosive power (the "Variable Inertia Training") with strength machines that use a motor and an electronic management system to simulate mass m variations in response to the kinematic parameters (position, velocity, and acceleration) of movement. This training modality can be designed to closely reproduce the kinematic and kinetic patterns occurring during ballistic or explosive sport movements, such as those occurring during throwing, hitting, rowing, and pushing activities. In addition, it may potentially enable the integrated development of the main neuromuscular components (force, rate of force development, and high-velocity strength) that contribute to the expression of explosive power for sports performance.